Social ties and individualization: A discussion about the possibilities of school learning - Palacios, Margarita; Cárdenas, Ana (Revista de Sociología, 2008)
The concepts of social ties and individualization shed light in this article to a discussion about how the main transformations that have taken place in the institutions of the family and work are related to the phenomenon of low school performance in Chile. More specifically, it is argued that the fractioning of symbolic horizons and the increasing weakening of social ties that are associated to the process of individualization, hinder the very "educability" of children, insofar the affective conditions required in learning, such as trust, belonging and certitude, are increasingly weakened in our society